Son of the Gamblin' Man : the Youth of an Artist - Sandoz, Mari, 1896-1966. (Lincoln : University of Nebraska Press, 2015)
The story tells of the gambler and townsite promoter who founded Cozad, Nebraska, and of his family, particularly his younger son, [who] became a world-famous artist and teacher known as 'Robert Henri.' This tale is essentially Robert's story, the story of a sensitive talented boy growing up in the midst of frontier violence. But it is also the story of the ambitious promoter and of frontier people fighting hunger, cold, blizzards, drouths, grasshoppers, prairie fires, and ruthless cattlemen. ...
Vendor-supplied metadata.
eBooks on EBSCOhost
Keywords: Cozad, John Jackson, -- 1830-1906 -- Fiction; Henri, Robert, -- 1865-1929 -- Fiction; Cozad, John Jackson, -- 1830-1906; Henri, Robert, -- 1865-1929; LITERARY CRITICISM -- American -- General; Fiction